2022
DOI: 10.1158/2159-8290.cd-22-1066
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Small-Molecule Inhibitor of KrasG12D in Immunocompetent Models of Pancreatic Cancer

Abstract: Mutations in the KRAS oncogene are found in more than 90% of patients with pancreatic ductal adenocarcinoma (PDAC), with Gly-to-Asp mutations (KRASG12D) being most common. Here, we tested the efficacy of a small molecule KRASG12D inhibitor, MRTX1133, in implantable and autochthonous PDAC models with an intact immune system. In vitro studies validated the specificity and potency of MRTX1133. In vivo, MRTX1133 prompted deep tumor regressions in all models tested, including complete or near-complete remissions af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 53 publications
7
119
0
Order By: Relevance
“…Our data suggest that T cells are not necessary to halt tumor progression upon Kras G12V elimination, but they contribute to achieving CRs. Similar results were reported in a recent study using an immunocompetent model of pancreatic ductal adenocarcinoma (PDAC) treated with the KRAS G12D inhibitor MRTX1133 ( 11 ). Notwithstanding the improved therapeutic efficacy of forthcoming KRAS inhibitors, their combination with checkpoint inhibitors or with selective inhibitors of upstream (SOS1, SHP2, RTKs) and downstream (MAPK pathway) effectors is likely to improve the efficacy of anti-KRAS therapies in the clinic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data suggest that T cells are not necessary to halt tumor progression upon Kras G12V elimination, but they contribute to achieving CRs. Similar results were reported in a recent study using an immunocompetent model of pancreatic ductal adenocarcinoma (PDAC) treated with the KRAS G12D inhibitor MRTX1133 ( 11 ). Notwithstanding the improved therapeutic efficacy of forthcoming KRAS inhibitors, their combination with checkpoint inhibitors or with selective inhibitors of upstream (SOS1, SHP2, RTKs) and downstream (MAPK pathway) effectors is likely to improve the efficacy of anti-KRAS therapies in the clinic.…”
Section: Discussionsupporting
confidence: 88%
“…Other KRAS G12C inhibitors, such as JDQ443, characterized by a novel binding mode, have been described as well as new compounds that inhibit KRAS noncovalently and independently of its GDP/guanosine triphosphate (GTP) state ( 8 , 9 ). Finally, a novel inhibitor, MRTX1133, selective for the KRAS G12D mutation and capable of blocking the KRAS oncoprotein in its “on” state, has been described ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…We show that MRTX1133 has significant impact on the growth of early stage tumors with tumor stasis observed in all human xenograft models, as also shown in other recent studies (Kemp et al, 2023). We demonstrate that MRTX1133 inhibits proliferation of PDAC cells and suppresses pERK, and such activity has a dominant impact on inducing tumor inhibition; While other studies have suggested that CD8 + T cells are not required for suppression of tumor growth in subcutaneous and orthotopic PDAC tumors, they involve short term experiments using mice with small tumor burden (Kemp et al, 2023). In this setting, it is likely tumor stasis due to suspended proliferation can appear effective but if all the cancer cells are not eliminated, tumor reemergence is possible.…”
Section: Discussionsupporting
confidence: 90%
“… 3 Although not yet ready for clinical use, this drug can provide valuable information in the pre-clinical setting, especially when applied to in vivo models that closely mimic the human disease. This is what the Stanger lab did in their recent work in Cancer Discovery , 1 where they studied the efficacy of MRTX1133 in immunocompetent murine models of pancreatic cancer. Kemp and colleagues use both implantable and spontaneous mouse models expressing the KRAS-G12D oncogene (the so-called KPC mice), in the presence of an intact immune system.…”
Section: Main Textmentioning
confidence: 81%
“… Mutation-selective KRAS inhibitors are revolutionizing the treatment of RAS-mutant tumors but cannot achieve durable effects alone. Kemp and colleagues 1 recently showed how the KRAS-G12D-specific inhibitor MRTX1133, while impairing cancer proliferation, stimulates T cell infiltration, which is crucial for sustained disease control. …”
mentioning
confidence: 99%